A roadmap to Vocational Education and Training Systems around the world - Eichhorst, Werner [Verfasser]; Rodriguez-Planas, Núria [Verfasser]; Schmidl, Ricarda [Verfasser]; Zimmermann, Klaus F. [Verfasser] (My University, 2012)
"With young people among the big losers of the recent financial crisis, vocational education and training (VET) is often seen as the silver bullet to the problem of youth joblessness. This paper provides a better understanding of VET around the world, dealing with three types of vocational systems: school-based education, a dual system in which school-based education is combined with firm-based training, and informal training. We first explore the motivation for these different types of training, before summarizing the institutional evidence, highlighting the key elements of each training system and discussing its main implementation strengths and challenges. We subsequently review the evidence on the effectiveness of VET versus general education and between the three VET systems. There are clear indications that VET is a valued alternative beyond the core of general education, while the dual system tends to be more effective than school-based VET. Informal training is effective, however relatively little is known of its relative strengths compared with other forms of vocational education." (Herausgeber; BIBB-Doku)
Keywords: S System beruflicher Bildung; S 1.3.3 Vollzeitschulische Berufsausbildung; S 1.3 Berufliche Erstausbildung; I 1 Internationale Berufsbildung; Berufsbildungssystem; Vergleich; Duales System; Anlernausbildung; Berufsausbildung; Schulische Berufsausbildung; Effektivität